2014
DOI: 10.1007/s00018-014-1701-5
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of nonclassical MHC-dependent invariant T cells

Abstract: TCR-mediated specific recognition of antigenic peptides in the context of classical MHC molecules is a cornerstone of adaptive immunity of jawed vertebrate. Ancillary to these interactions, the T cell repertoire also includes unconventional T cells that recognize endogenous and/or exogenous antigens in a classical MHC-unrestricted manner. Among these, the mammalian nonclassical MHC class I-restricted invariant T cell (iT) subsets, such as iNKT and MAIT cells, are now believed to be integral to immune response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 139 publications
(187 reference statements)
1
13
0
Order By: Relevance
“…Recent work focusing on one of the isotypes, xnc10, has shown that NKT cells bearing an invariant TCR α-chain use this class Ib molecule as a restricting element, aiding in responses to tumour and viral antigens (see below for clarification; mammalian NKT cells use the nonclassical MHC class I molecules CD1 and MR1 as restricting elements 129 ). Ancient nonclassical class I lineages in bony fish and cartilaginous fish are candidates for recognition by NKT-like cells or for other non-immune functions as shown in mammals 130,131 . For example, despite the general rapid evolution of the bony fish, there are deep lineages of MHC class I molecules, especially the so-called Z lineage in which the peptide-binding region is extremely conserved in all species 132 .…”
Section: Evolution Of the Mhcmentioning
confidence: 99%
“…Recent work focusing on one of the isotypes, xnc10, has shown that NKT cells bearing an invariant TCR α-chain use this class Ib molecule as a restricting element, aiding in responses to tumour and viral antigens (see below for clarification; mammalian NKT cells use the nonclassical MHC class I molecules CD1 and MR1 as restricting elements 129 ). Ancient nonclassical class I lineages in bony fish and cartilaginous fish are candidates for recognition by NKT-like cells or for other non-immune functions as shown in mammals 130,131 . For example, despite the general rapid evolution of the bony fish, there are deep lineages of MHC class I molecules, especially the so-called Z lineage in which the peptide-binding region is extremely conserved in all species 132 .…”
Section: Evolution Of the Mhcmentioning
confidence: 99%
“…In addition, unlike zebrafish, T cells develop within 2 weeks of age in X. laevis tadpoles. Furthermore, the majority of these T cells are so-called innate T cells expressing semi-invariant T cell receptors that are restricted by MHC class-I-like molecules [reviewed in (Edholm et al 2014; Robert and Edholm 2014)]. Specifically, deep-sequencing has revealed that 80% of CD8 intermediate and CD8 negative T cells express 6 invariant TCRα rearrangements (Edholm et al 2013).…”
Section: 3 Evolutionary Conservation Of M1/m2-like Functional Hetermentioning
confidence: 99%
“…This observation can at least partly be explained by the expression of several distinct XNC genes in the tadpole thymus at the onset of thymic organogenesis ((Goyos et al 2011); Edholm and Robert, unpublished observation). Many of these XNCs are preferentially expressed on thymocytes, and their gene expression is maintained through metamorphosis as well as in the fully matured adult thymus ((Edholm et al 2014b); Edholm and Robert, unpublished observation). These expression patterns suggest that tadpoles have a functional and specialized larval T cell compartment that follows a differentiation program distinct from that of the adult.…”
Section: Insight Into the Evolution Of Mhc Class I-like-restricted Itmentioning
confidence: 99%